MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS BELAJAR SISWA DENGAN PENERAPAN PEMBELAJARAN OPEN ENDED PROBLEM (MASALAH BERAKHIR TERBUKA) MATA PELAJARAN IPS POKOK BAHASAN TINDAKAN EKONOMI DI KELAS VII-D SEMESTER I SMP NEGERI 1 MANGARAN - Nursalam Nursalam (STKIP PGRI SITUBONDO, 2014)
Given the teaching method as one of the things that affects student activities in participating in learning and also learning outcomes, a teacher must be able to apply the right method. Based on the various problems that occurred in grade VII, the teacher should start trying to apply the appropriate learning method, which is already agreeing to apply open-ended learning. Qualitative descriptive research method. The research location is SMP Negeri 1 Mangaran Situbondo. Collecting data using interviews, documentation and observation. The analysis in this research is to use qualitative descriptive analysis. The application of Open Ended Problem Learning (Open Ended Problems) can improve learning outcomes with completeness of student learning outcomes reaching as much as 87% in social studies subjects, the subject of economic action in class VII-D semester I SMP Negeri 1 Mangaran. With the application of Open Ended Problem learning, it can increase learning activities to reach a percentage of 85% in the social studies subject, the subject of economic action in class VII-D semester I of SMP Negeri 1 Mangaran.